Kinerja Tenaga Administrasi Sekolah Menengah Atas Se-Kabupaten Sijunjung - Widyawati (Institut Agama Kristen Negeri Manado, 2022)
This research is motivated by the low performance of school administration staff in Sijunjung district. The purpose of this research is to get an overview of the performance of administrative staff. This type of research is a quantitative research, which has a population of 90 school administrators. From the results of the calculation of the sample used amounted to 78 school administration staff. In this study, the instrument used was a questionnaire with a likert scale. Descriptive analysis to calculate the mean value, level of achievement of respondents and categories. Performance is categorized into high category, with an average of 87.14%. The benchmarks for performance are responsibility, cooperation and initiative. For this reason, the performance of administrative staff must be high so that the goals of the organization can run effectively and efficiently